Analisis Inklusivisme Islam dalam Lanskap Interaksi Sosial Keagamaan: Perspektif Tafsīr al-Wasīṭ li al-Qur’ān al-Karīm karya Sayyid Thantawi - A. Zaeini Misbaahuddin Asyuari; Hilmi Husaini Zuhri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the construction of Islamic inclusivism in Muhammad Sayyid Thantawi’s Tafsīr al-Wasīṭ as a response to the growing religious tensions driven by exclusivism and theological misunderstanding worldwide, including in Indonesia. The novelty of this research lies in its comprehensive analysis of a modern Qur’anic commentary rarely explored through the lens of interreligious relations, particularly regarding how Thantawi interprets verses on tolerance and religious diversity. Using a qualitative library-based approach, this study critically analyzes Thantawi’s interpretations of Qur’anic passages concerning the divine will of human diversity, freedom of religion, ethical methods of da‘wah, and the protection of non-Muslim places of worship, while comparing them with classical and modern exegetical perspectives. The findings reveal that Thantawi maintains a tafsīr bi al-ma’tsūr framework yet integrates comparative reasoning, producing an inclusivist model that upholds Islamic theological distinctiveness without embracing pluralism. The study concludes that Thantawi’s inclusivism offers significant relevance for strengthening interreligious harmony in Indonesia and contributes to expanding contemporary Qur’anic studies on Muslim–non-Muslim relations.